Inflammatory Immune Process and Depression-like Behavior in Hypothyroid Rats: A [18F] DPA-714 Micro Positron Emission Tomography Study - Yizhen Wang; Aijuan Tian; Fang Zhang; Jing Yu; Jianer Ling (MDPI AG, 2023)
Hypothyroidism is closely related to mental disorders, mainly depression, through an as-yet-unknown mechanism. The cerebral inflammatory immune process has been implied to play a pivotal role in the onset of affective symptoms in several conditions. In order to gain insight into the mechanism underlying the depressive behaviors in hypothyroid rats, brain microglial activation was evaluated using micro positron emission tomography imaging with a translocator protein (TSPO) radioligand. Hypothyroidism was induced in adult male Wistar rats by administration of 0.05% propylthiouracil in drinking water for five weeks. Open field, forced swimming and tail suspension tests were employed to evaluate the depressive behavior in hypothyroid rats, and the relationship between the behavioral changes and brain microglial activation was evaluated using [18F] DPA-714 micro positron emission tomography imaging. The open field test revealed significantly reduced first-minute activity and rearing behavior in the hypothyroid group, as well as significantly increased immobility in the forced swimming test and the tail suspension test. Hypothyroidism induced significantly increased microglial activation in the hippocampus. The radioligand uptake in the hippocampus correlated negatively with first-minute activity in the open field test (p < 0.05), and the radioligand uptake in the hippocampus correlated positively with changes in the immobility time in the forced swimming test and the tail suspension test (p < 0.05). Immunohistochemistry also confirmed the activation of microglia and inflammatory bodies in hypothyroid rats. The results indicate that hypothyroidism can induce depressive behavior in adult Wistar rats, microglial activation in the hippocampus plays an important role in the depressive behavior in hypothyroid rats and the inflammatory immune mechanism may underlie the behavioral abnormalities in thyroid dysfunction. Furthermore, the findings in the present study suggest there might be a common mechanism underlying depressive behavior in adult-onset hypothyroidism and depression.